In a sequence of real numbers x 0 , x 1 , x 2 , x 3 , … , x 9 9 , x 1 0 0 , for every pair of integers a , b , such that 0 ≤ a < b ≤ 1 0 0 , the sum x a + x b is a + b less than the sum of the other 99 numbers in the sequence.
As an explicit example, x 0 + x 1 = x 2 + x 3 + x 4 + ⋯ + x 1 0 0 − ( 0 + 1 )
If the value of x 5 0 can be expressed in the form n m for co-prime positive integers m , n , find the value of m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just to add on: x n = 9 7 2 5 2 5 − 2 1 n
Great solution though, I used a much more tedious method involving a recurrence relation.
Log in to reply
It might just be a vocab thing, but I don't know what recurrence relation is, so if it isn't too awful to share your solution, please do so!
Log in to reply
I'll post a solution in the inspired problem, so you can see my method.
I think that is 2 − n instead of 2 − x .... Same approach !
no need to add all the equations. just add 101.i solved it just before my ict exam started in the classs. nice problem!
Log in to reply
Since there are an odd number of therms, I'm not seeing exactly what you did. Could you please show me?
Log in to reply
2 ( x 0 + x 1 ) = S − 0 − 1 2 ( x 1 + x 2 ) = S − 1 − 2 2 ( x 2 + x 3 ) = S − 2 − 3 ..... 2 ( x 9 9 + x 1 0 0 = S − 9 9 − 1 0 0 2 ( x 1 0 0 + x 0 ) = S − 1 0 0 − 0 adding them up we get 2 ( 2 S ) = 1 0 1 S − 2 1 0 0 ( 1 0 0 + 1 ) − 2 1 0 0 ( 1 0 0 + 1 ) = 1 0 1 S − 1 0 1 0 0 we can solve this to get 9 7 S = 1 0 1 0 0 ⟹ S = 9 7 1 0 1 0 0 i solved for x 5 0 like this: 2 ( x 5 0 + x 0 ) = S − 5 0 − 0 2 ( x 5 0 + x 1 ) = S − 5 0 − 1 ...... 2 ( x 5 0 + x 9 9 ) = S − 5 0 − 9 9 2 ( x 5 0 + x 1 0 0 ) = S − 5 0 − 1 0 0 add all up to find 2 ( 1 0 1 x 5 0 + S ) = 1 0 1 S − 1 0 1 ∗ 5 0 − 2 1 0 0 ( 1 0 0 + 1 ) = 1 0 1 S − 1 0 1 0 0 the rest is easy.
Log in to reply
@Aareyan Manzoor – Ah okay now I see, you loop the 100 back to the 0. I can't believe I didn't think of that!
Log in to reply
@Brandon Monsen – another interesting thing is that 1 0 1 s − 1 0 1 0 0 = 4 s . we could substitute that in the last line to make it more easy!
@Brandon Monsen – just posted this , which is based of this problem. please try!
@Aareyan Manzoor – Nice!
Hi Brandon Sir nice solution, I used x 1 , x 2 , x 5 0 . Were you inspired from this problem?
Good analysis used to determine the general term.
L e t S = i = 0 ∑ 1 0 0 X i . X a + X b = S − ( X a + X b ) − ( a + b ) ⟹ X a + X b = 2 S − 2 a + b ⟹ X i = 4 S − 2 i , 0 ≤ i ≤ 1 0 1 . S = i = 0 ∑ 1 0 0 X i = i = 0 ∑ 1 0 0 ( 4 S − 2 i ) = 4 1 0 1 S − 2 5 0 ∗ 1 0 1 . ∴ 4 9 7 S = 2 5 ∗ 1 0 1 . ⟹ S = 9 7 4 ∗ 2 5 ∗ 1 0 1 . X 5 0 = 4 S − 2 5 0 = 9 7 2 5 ∗ 1 0 1 − 2 5 = 9 7 4 ∗ 2 5 = n m . m + n = 1 9 7
Problem Loading...
Note Loading...
Set Loading...
Let S denote the sum of all of the terms in the sequence.
By the given information, we know that
x a + x b = S − x a − x b − a − b 2 x a + 2 x b = S − a − b
Note that there are ( 2 1 0 1 ) ways we can pair up two numbers in this sequence. Also note that there are 100 ways to pair a 0 ; once with x 1 , once with x 2 , and so on. This holds for any x p , a and b .
This means if we sum up our above equation for all possible combinations of two terms of our sequence, we will get
2 0 0 ( x 0 + x 1 + x 2 + . . . + x 1 0 0 ) = ( 2 1 0 1 ) S − 1 0 0 k = 0 ∑ 1 0 0 k
Here, we can simplify and get
2 0 0 S = 5 0 5 0 S − ( 5 0 ) ( 1 0 0 ) ( 1 0 1 ) 4 8 5 0 S = 5 0 5 0 0 0 S = 9 7 1 0 1 0 0 S = 1 0 4 + 9 7 1 2
Now, we can set up the following system:
2 ( x 4 9 + x 5 0 ) = 1 0 4 + 9 7 1 2 − 4 9 − 5 0 = 5 + 9 7 1 2 2 ( x 4 9 + x 5 1 ) = 4 + 9 7 1 2 2 ( x 5 0 + x 5 1 ) = 3 + 9 7 1 2
Subtract the second equation from the first to get
2 x 5 0 − 2 x 5 1 = 1 2 x 5 0 + 2 x 5 1 = 3 + 9 7 1 2
Add the two equations together to get
4 x 5 0 = 4 + 9 7 1 2 x 5 0 = 9 7 1 0 0
Since 100 and 97 are co-prime, our answer is 9 7 + 1 0 0 = 1 9 7
As for the problem's title, the sequence actually turns out to be an arithmetic sequence, with each successive term decreasing by 2 1